PENGASUHAN ANAK PASCA PERCERAIAN DALAM PERSPEKTIF HUKUM KELUARGA ISLAM - Muhammad Abil Anam; Yushinta Eka Farida (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Child care after divorce is an important aspect in the context of Islamic family law. This article examines various aspects of parenting after divorce, with a focus on the Islamic legal framework. Through an analysis of the perspective of Islamic family law, this article discusses the rights and obligations of parents towards children, the role of the court in determining parenting, as well as the principles that guide the process of parenting children after divorce. This research aims to provide an in-depth understanding of Islamic family law concepts related to child care, as well as their implications for children's welfare in divorce situations. The conclusion of this article provides insight into how Islamic family law regulates child care after divorce by paying attention to legal, ethical aspects and the best interests of the child.